2021
DOI: 10.1088/1478-3975/ac267a
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic pressure maintains epithelial integrity and inhibits cell motility

Abstract: Cytoplasmic pressure, a function of actomyosin contractility and water flow, can regulate cellular morphology and dynamics. In mesenchymal cells, cytoplasmic pressure powers cell protrusion through physiological three-dimensional extracellular matrices. However, the role of intracellular pressure in epithelial cells is relatively unclear. Here we find that high cytoplasmic pressure is necessary to maintain barrier function, one of the hallmarks of epithelial homeostasis. Further, our data show that decreased c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Previous in vitro studies have shown that several cell behaviors, from cell migration 26,53 to cortical cell mechanics 17 as well as cell and nuclear size 13 , depend on the cell's osmotic pressure. Other works have shown the existence of spatial gradients in extracellular spaces that lead to gradients in tissue stiffness during posterior body axis elongation in zebrafish 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro studies have shown that several cell behaviors, from cell migration 26,53 to cortical cell mechanics 17 as well as cell and nuclear size 13 , depend on the cell's osmotic pressure. Other works have shown the existence of spatial gradients in extracellular spaces that lead to gradients in tissue stiffness during posterior body axis elongation in zebrafish 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous measurements of the hydrostatic pressure difference across the cell surface in animal cells in vitro, or in externally accessible lumens in vivo, have been achieved using either microneedles as a pressure gauge or other surface contact probes, such as atomic force microscopy 16,[26][27][28][29] . These techniques require an external probe to be in constant contact with the sample, which is invasive and not well-suited for 3D multicellular systems that continuously change shape.…”
mentioning
confidence: 99%
“…Previous in vitro studies have shown that several cell behaviors, from cell migration 26,48 to cortical cell mechanics 17 as well as cell and nuclear size 13 , depend on the cell's osmotic pressure. Other works have shown the existence of spatial gradients in extracellular spaces that lead to gradients in tissue stiffness during posterior body axis elongation in zebrafish 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous measurements of the hydrostatic pressure difference across the cell surface in animal cells in vitro, or in externally accessible lumens in vivo, have been achieved using either microneedles as a pressure gauge or other surface contact probes, such as atomic force microscopy 16,[26][27][28] . These techniques require an external probe to be in constant contact with the sample, which is invasive and not well-suited for 3D multicellular systems that continuously change shape.…”
mentioning
confidence: 99%
“…Turgor pressure is a primary determinant of mechanical properties of walled cells of various biological kingdoms including plants, fungi, bacteria, and protists (Shabala et al ., 2009; Beauzamy et al ., 2014). Turgor pressures also contribute to mechanical properties and cell shape determination in animal cell systems (Jones et al ., 2021; Vian et al ., 2022). Turgor pressure (also known as hydrostatic pressure) is the internal pressure relative to the outside environment of the cell; this internal pressure arises largely from the concentration of osmotic solutes such as ions, amino acids, and small metabolites.…”
Section: Introductionmentioning
confidence: 99%